Elevated fruit nitrogen impairs oil biosynthesis in olive (Olea europaea L.) - Erel, Ran; Yermiyahu, Uri; Yasuor, Hagai; Ben-Gal, Alon; Zipori, Isaac; Dag, Arnon (Frontiers in Plant Science, 2023)
Oil in fruits and seeds is an important source of calories and essential fatty acids for humans. This specifically holds true for olive oil, which is appreciated for its superior nutritional value. Most olive orchards are cultivated to produce oil, which are the outcome of fruit yield and oil content. Little information is available on the effect of nitrogen (N) on olive fruit oil content. The response of olive trees to different rates of N was therefore studied in soilless culture (3 years) and commercial field (6 years) experiments. In both experiments, fruit N level and oil biosynthesis were negatively associated. Fruit N increased in response to N fertilization level and was inversely related to fruit load. The negative correlation between fruit N and oil content was more pronounced under high fruit load, indicating sink limitation for carbon. These results agree with those reported for oilseed crops for which a trade-off between oil and protein was proposed as the governing mechanism for the negative response to elevated N levels. Our results suggest that the protein/oil trade-off paradigm cannot explain the noticeable decrease in oil biosynthesis in olives, indicating that additional mechanisms are involved in N-induced inhibition of oil production. This inhibition was not related to the soluble carbohydrate levels in the fruit, which were comparable regardless of N level. These results emphasize the importance of balanced N nutrition in oil-olive cultivation to optimize production with oil content.